PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA HARD ROCK HOTEL BALI - Surya Diputra, Ida Bagus Gede; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.03.NO.05 TAHUN 2014, 2014)
ABSTRACT This study examines the relationship among organizational culture, job satisfaction and employee motivation at the Hard Rock Hotel Bali. The research objectives are 1) To determine the effect of organizational culture on job satisfaction at the Hard Rock Hotel Bali 2) To determine the effect of job satisfaction on employee motivation at the Hard Rock Hotel Bali 3) To determine the effect of organizational culture on employee motivation at Hard Rock Hotel Bali. Respondents in this study were 200 employees of Hard Rock Hotel Bali. This study used analysis of Structural Equation Modeling (SEM) with the application software Analysis of Moment Structure (AMOS) and the Special Package for StatisticsScience (SPSS). The results showed that 1) organizational culture has positive and significant effect on job satisfaction of employees at the Hard Rock Hotel Bali. 2) job satisfaction has positive and significant impact on employee motivation at the Hard Rock Hotel Bali. 3) organizational culture has positive and significant impact on employee motivation at the Hard Rock Hotel Bali. The implication of this research is to improve the existing organizational culture, so the aspect of job satisfaction can be met, because generally high employee job satisfaction can increase employee motivation. Key Word : organizational culture, job satisfaction and employee motivation